SAVINGS INVESTMENTS IN SHARIA BANKS IN THE PERSPECTIVE OF SHARIAH ECONOMIC LAW (CASE STUDY AT â€œBANK SYARIAH BUKOPINâ€) - Samsudin, Agus Rojak; Athoillah, Mohamad Anton (Journal of Economicate Studies, 2017)
There are three motives a person to save funds through savings in the Conventional Bank: security, plans and investment. Implementation of interest system in Conventional banks is a very fundamental constraint for a Muslim to invest his funds in the bank. Because in the view of the scholars of the flower system is identical with the usury (riba) that is forbidden in Islam. It turns out long before the birth of money storage system in conventional bank interest, in classical fiqh literature known the concept and theory of al wadiah and mudharabah which is substantially no differences from the savings and investment savings offered by conventional banks. This paper discusses the theory, concepts and implementation of al wadiah as non-interest investment savings applied in sharia bank in the perspective of shariah economic law, by looking at case examples of the saving products of Bank Syariah Bukopin (BSB). It was found that all investment contracts in savings products offered by BSB were in accordance with the principles of shariah; as outlined in the Qur'an and Sunnah as the basis of Shariah, as well as Law Number 21 Year 2008 and Law no. 10 year 1998, Bank Indonesia Regulation (Peraturan Bank Indonesia [PBI]), Compilation of Islamic Economic Law (Kompilasi Hukum Ekonomi Syariah [KHES]) and Fatwa of National Sharia Board (Dewan Syariah Indonesia [DSN]) Indonesian Council of Ulama (Majelis Ulama Indonesia [MUI])